(untitled) (International Seven Journal of Multidisciplinary, 2024)
Urban construction and demolition (C&D) activities generate large volumes of debris that, when managed through fragmented and poorly coordinated logistics systems, produce significant environmental impacts. Diffuse logistics characterized by decentralized waste generation, informal transport, and irregular disposal pathways intensify greenhouse gas emissions, promote illegal dumping, and undermine material recovery and circular economy objectives. This article examines the environmental consequences associated with diffuse C&D waste logistics in urban contexts and discusses strategies through which cities can mitigate these negative effects. Drawing on academic literature and institutional reports, the analysis highlights the roles of regulatory frameworks, economic incentives, infrastructure investment, and social inclusion in improving environmental performance. The findings suggest that transforming diffuse waste flows into structured material management systems can substantially reduce emissions, conserve natural resources, and support sustainable urban development.